2016
DOI: 10.1530/jme-15-0310
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase expression and regulation in breast and endometrial cancer

Abstract: Long-term exposure to excess estrogen increases the risk of breast cancer and type 1 endometrial cancer. Most of the estrogen in premenopausal women is synthesized by the ovaries, while extraovarian subcutaneous adipose tissue is the predominant tissue source of estrogen after menopause. Estrogen and its metabolites can cause hyperproliferation and neoplastic transformation of breast and endometrial cells via increased proliferation and DNA damage. Several genetically modified mouse models have been generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(150 citation statements)
references
References 123 publications
(67 reference statements)
4
144
1
1
Order By: Relevance
“…27 The positive feedback of E 2 /ERα signaling is vital to the formation of predominant follicles in the ovary. 34 It was reported that miR-22 was present in the ovary. 35,36 It is most likely that the interaction mechanism between androgen and estrogen also works in the ovary, just as what we found in the placenta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The positive feedback of E 2 /ERα signaling is vital to the formation of predominant follicles in the ovary. 34 It was reported that miR-22 was present in the ovary. 35,36 It is most likely that the interaction mechanism between androgen and estrogen also works in the ovary, just as what we found in the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…The membranes were blocked with 5% non-fat milk or 30 1% BSA in TBS-T (20 mM Tris-HCl, pH 7.4, 150 mM NaCl, and 0.1% Tween-20) and 31 incubated with the appropriate antibodies, following by the corresponding horseradish 32 peroxidase (HRP)-conjugated secondary antibody (Promega, Madison, WI). The signals were 33 visualized using an ECL kit (Thermo Scientific, MA, USA), followed by exposure to X-ray 34 film (Kodak, NY, USA) and analysis using Quantity One ® 1-DAnalysis Software, version 4.4 35 (Bio-Rad, CA, USA). The relative density of each specific molecule was measured by 36 densitometry, and its value was compared with the GAPDH or -actin value from the same blot.…”
Section: Sources Of Fundingmentioning
confidence: 99%
“…71,72 These promoter regions drive aromatase expression in the ovaries and bone, adipose, placental, and neuronal tissue. Human CYP19A1 has at least eight different transcriptional start sites encoding unique upstream exons, each of which is specific to a different tissue.…”
Section: The Role Of Estrogens In the Microenvironment And Their Inflmentioning
confidence: 99%
“…First, the endometrial implants have intrinsic aromatase activity, which leads to the conversion of cholesterol to estradiol. 12 The endometrium is rich in PG-E2 receptors and activation of the PG receptor subtype EP-2 leads to activation of cyclic AMP, which increases the expression of key steroidogenic genes, and aromatase activity eventually leading to increased estradiol production. Along with intrinsic aromatase activity estradiol produced from ovary and peripheral fat also reaches the sites of endometriosis.…”
Section: Medical Management Of Endometriosismentioning
confidence: 99%